1994
DOI: 10.1007/bf01094789
|View full text |Cite
|
Sign up to set email alerts
|

Body mass, body composition and sleeping metabolic rate before, during and after endurance training

Abstract: Metabolic rate, more specifically resting metabolic rate (RMR) or sleeping metabolic rate (SMR), of an adult subject is usually expressed as a function of the fat-free mass (FFM). Chronic exercise is thought to increase FFM and thus to increase RMR and SMR. We determined body mass (BM), body composition, and SMR before, during, and after an endurance training programme without interfering with energy intake. The subjects were 11 women and 12 men, aged 37 (SD 3) years and body mass index 22.3 (SD 1.5) kg.m-2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 23 publications
4
36
1
2
Order By: Relevance
“…In our study, fat scores for exercisetrained and control groups were not significantly different, so increases in lean mass, including M pec , were major components of the elevated M b . A similar reduction in BMR after training, despite stable or increasing M b , has also been observed in mammals (Westerterp et al, 1994;Hoppeler et al, 1995).…”
Section: Among Birds Tufted Duckssupporting
confidence: 75%
“…In our study, fat scores for exercisetrained and control groups were not significantly different, so increases in lean mass, including M pec , were major components of the elevated M b . A similar reduction in BMR after training, despite stable or increasing M b , has also been observed in mammals (Westerterp et al, 1994;Hoppeler et al, 1995).…”
Section: Among Birds Tufted Duckssupporting
confidence: 75%
“…The longest training intervention showed the biggest absolute change in FFM without any indication of an increase in RMR. In fact, the opposite was measured, SMR was slightly lower, whereas FFM had increased by 5%, at 40 wk after the start of the training program (21). Here, the speculation was that RMR changed as a defense mechanism of the body weight maintenance.…”
Section: Effect Of Exercise Intervention On Daily Energy Turnover Andmentioning
confidence: 87%
“…Goran and Poehlman (16) observed an increase in RMR from 6.68 to 7.38 MJ/d. Westerterp et al (17,21) observed a tendency for SMR to decrease from (x -± SD) 6.46 ± 0.62 to 6.32 ± 0.61 MJ/d. Van Etten et al (18) did not observe any change in SMR.…”
Section: Effect Of Exercise Intervention On Daily Energy Turnover Andmentioning
confidence: 99%
“…Some studies have shown an increase in resting metabolic rate, adjusted for fat-free mass and fat mass, in response to training [7][8][9] whereas others found no effect. [10][11][12] In contrast to these studies, not much research has been focused on establishing the most beneficial exercise intensity for increasing 24 h energy expenditure 24 h EE. Some studies have shown that HI exercise has a more pronounced effect on postexercise energy expenditure compared to LI exercise, [13][14][15] whereas other found no difference, 16,17 but these studies only measured energy expenditure for several hours after exercise.…”
Section: Introductionmentioning
confidence: 99%